2014
DOI: 10.1093/ofid/ofu085
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Carbon Monoxide to Carbon Dioxide Ratio in the Exhaled Breath of Mice Treated With a Single Dose of Lipopolysaccharide

Abstract: By gas chromatographic analysis, the ratio of carbon monoxide to carbon dioxide increased in exhaled breath of 2 mouse strains injected with different doses of Escherichia coli lipopolysaccharide. The ratios correlated with inflammation biomarkers and heme oxygenase-1 expression in blood.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…Overall, the profile of the analyte changes in the infected immunocompetent mice corresponds to a marked systemic inflammatory response and an accompanying modulation of those pro-inflammatory cytokines and chemokines by anti-inflammatory cytokines, such as IL-10. There were several similarities to and some differences from the early responses of mice to injections of E. coli lipopolysaccharide (LPS) [ 96 ]. More specifically, 4 h after injection the LPS-treated mice showed marked elevations of both IL-6 and IL-10, and while IL-6 had declined toward normal by 24 h after injection, IL-10 remained elevated.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the profile of the analyte changes in the infected immunocompetent mice corresponds to a marked systemic inflammatory response and an accompanying modulation of those pro-inflammatory cytokines and chemokines by anti-inflammatory cytokines, such as IL-10. There were several similarities to and some differences from the early responses of mice to injections of E. coli lipopolysaccharide (LPS) [ 96 ]. More specifically, 4 h after injection the LPS-treated mice showed marked elevations of both IL-6 and IL-10, and while IL-6 had declined toward normal by 24 h after injection, IL-10 remained elevated.…”
Section: Resultsmentioning
confidence: 99%
“…Accurate measurements of exhaled gases requires normalization for minute volumes using the rate of CO 2 production [48]. We found that ATP injection stimulated the release of volatile organic molecules ranging from 1 to 5 carbons in length in the rst 10 minutes ( Figure 3A-H).…”
Section: Overviewmentioning
confidence: 89%
“…Breathomic analysis of natural gases and volatile organic compounds in mice was performed as described with minor modi cations [48]. Six 10-month old C57BL/6J male mice were used in this study.…”
Section: Breathomicsmentioning
confidence: 99%
“…Lipopolysaccharide (LPS)—the major component of the outer membrane of gram-negative—is released from leaky gut and represents one of the primary mechanisms for induction inflammatory response and metabolic endotoxemia. Mice and rats injected with LPS purified from E. coli are ideal models for the study of inflammation and systemic sepsis ( Bos et al., 2013 ; Langeroudi et al., 2014 ). In one study with septic mice induced by LPS, it was observed that there were increased levels of carbon monoxide (CO) and ratio of CO to CO 2 in a dose-responsive manner within hours after injection ( Langeroudi et al., 2014 ).…”
Section: Voc Signatures Emitted In Bacterial Sepsismentioning
confidence: 99%